(untitled) (Colombia Medica, 2006)
Background: The Zung´s self-rating depression scale has been used in various Colombian studies among adolescents. However, its construct validation has not been yet reported. Objective: To validate the construct of the Zung´s self-rating depression scale in adolescent attending a low income public school at the city of Cartagena, Colombia. Method: A total of 408 students aged 13-17 years old (mean 14.7 years) completed the Zung´s self-rating depression scale considering the last two weeks, in the classroom, 50% boys and 50% girls. Internal consistency and factor analysis were computed. Results: The Cronbach’s alpha test was 0.689. The first factor (depressive mood) explained 15.8% of the variance and the second factor (cognitive and somatic complaints) accounted for 9.1% of the variance. Conclusions: The Zung´s self-rating depression scale in adolescents exhibits an acceptable internal consistency and a construct of two principal factors, like in adults.